Developing online teaching skills for the 21st century classroom - Stanojević, Mateusz-Milan; Ernest, Pauline (2012)
Developing Online Teaching Skills, DOTS (http://dots.ecml.at/) is a project supported by the Council of Europe's European Centre for Modern Languages (www.ecml.at). Its first aim was to create an online toolkit and an online training space for language professionals who want to engage with online teaching. In the second phase, DOTS and its follow-up project More DOTS, are providing Targeted Support activities, e.g. workshops or presentations, on request. DOTS activities are based on an analysis of the needs of language teachers faced with an increasing requirement to move teaching and learning online, apply the latest technologies and keep abreast with the latest developments. This workshop targets teachers, teacher trainers and decision makers, and is designed to raise their awareness of the need for an approach to ICT which integrates pedagogy with technology. It fosters discussions between the participants on their strengths and training needs. It supports self-training, which helps language professionals develop the necessary skills in an online Moodle workspace, and provides graded and supported tasks as well as interactive spaces for the exchange of experiences and ideas.
ENG